Communicative Culture of Public Administration of Modern Ukraine: Theory, Methodology, Research Outcomes - Larysa Lytvynova (Technium Social Sciences Journal, 2020)
The article is devoted to the study of the communicative culture of public administration of modern Ukraine. It analyzes modern theoretical and methodological approaches to the study of the phenomenon of communicative culture and substantiates the necessity of applying an interdisciplinary approach in research. An integrated model of formation of communicative culture in public administration is presented and described as a system of organization and implementation of purposeful and indirect influences that ensure the effectiveness of communication and interchanges, which allows to achieve the result in the form of postmodern communicative culture in public administration. Communicative culture in the proposed model is interpreted as an integral unity of socially oriented and reflexive competencies and is implemented at the theoretical-methodological, praxeological-substantive, reflexive-effective and public-communicative levels. The article presents research outcomes of studying communicative culture in public administration in Ukraine. It also substantiates the necessity of restructuring the culture of communications towards the acquisition of socially oriented and socially reflexive competencies and the values of openness, cooperation, cohesion and democracy.